Are the St John's wort Hyp‐1 superstructures different?. Issue 6 (24th May 2021) - Lovelace, Jeffrey J.; Borgstahl, Gloria E. O.
Abstract : Two modulated structures of the Hyp‐1–ANS complex with different unit‐cell dimensions and contents were analyzed in (3+1)D superspace, revealing that they are very similar if not the same higher‐dimensional structure with a slight shift in the q vector being responsible for the differences observed in 3D space. Abstract : Two commensurately modulated structures (PDB entries 4n3e and 6sjj ) were solved using translational noncrystallographic symmetry (tNCS). The data required the use of large supercells, sevenfold and ninefold, respectively, to properly index the reflections. Commensurately modulated structures can be challenging to solve. Molecular‐replacement software such as Phaser can detect tNCS and either handle it automatically or, for more challenging situations, allow the user to enter a tNCS vector, which the software then uses to place the components. Although this approach has been successful in solving these types of challenging structures, it does not make it easy to understand the underlying modulation in the structure or how these two structures are related. An alternate view of this problem is that the atoms and associated parameters are following periodic atomic modulation functions (AMFs) in higher dimensional space, and what is being observed in these supercells are the points where these higher dimensional AMFs intersect physical 3D space. In this case, the two 3D structures, with a sevenfold and a ninefold superstructure, seem to be quite different. However, describing those structures within the higher dimensional superspace approach makes a strong case that they are closely related, as they show very similar AMFs and can be described with one unique (3+1)D structure, i.e. they are two different 3D intersections of the same (3+1)D structure.